2019
DOI: 10.1038/s41467-019-08657-5
|View full text |Cite
|
Sign up to set email alerts
|

eg occupancy as an effective descriptor for the catalytic activity of perovskite oxide-based peroxidase mimics

Abstract: A peroxidase catalyzes the oxidation of a substrate with a peroxide. The search for peroxidase-like and other enzyme-like nanomaterials (called nanozymes) mainly relies on trial-and-error strategies, due to the lack of predictive descriptors. To fill this gap, here we investigate the occupancy of eg orbitals as a possible descriptor for the peroxidase-like activity of transition metal oxide (including perovskite oxide) nanozymes. Both experimental measurements and density functional theory calculations reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
171
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(192 citation statements)
references
References 50 publications
7
171
0
1
Order By: Relevance
“…(1). In addition, Xiaoyu Wang et al 56 showed recently that the population of e g orbitals plays a fundamental role in the peroxidase-like catalytic activity of perovskite oxide-based nanosystems.…”
Section: Discussionmentioning
confidence: 99%
“…(1). In addition, Xiaoyu Wang et al 56 showed recently that the population of e g orbitals plays a fundamental role in the peroxidase-like catalytic activity of perovskite oxide-based nanosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Gold nanoparticles (AuNPs) exhibit GOX‐like activity that can decompose glucose into gluconic acid and H 2 O 2 (Luo et al., ). Recent studies revealed that the multiple nanozyme activities are a possible consequence of a huge collection of active nanostructures, which precisely manipulate the distribution and arrangements of different atoms inside to mediate redox cycles and electron‐transfer communications during catalysis (Wang, Guo et al., ).…”
Section: Principles Of Detection Using Enzyme‐mimetic Nanomaterialsmentioning
confidence: 99%
“…Regarding the efficiency of such as catalysis, Wang et al recently showed that e g orbital (d x2-y2 and d z2 ) occupancy could be an excellent measure of peroxidase like activity of transition metal oxide nanozymes 44 . Their study established a volcano relationship of activity with the average e g occupancy on a salce of 0--2.…”
Section: Main Textmentioning
confidence: 99%